1983
DOI: 10.1021/bi00273a031
|View full text |Cite
|
Sign up to set email alerts
|

Water catalysis of peptide hydrogen isotope exchange

Abstract: The temperature dependence of the hydrogen-tritium and deuterium-hydrogen exchange reactions in poly(DL-alanine) has been reexamined. The results indicate a significant contribution to the observed exchange rates from the water-catalyzed reaction at pD values near pDmin. The activation enthalpy for water-catalyzed deuterium-hydrogen exchange in poly(DL-alanine) is found to be 21 kcal mol-1. As a result, the contribution to the observed exchange rate from the water-catalyzed reaction increases with increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Water catalysis has been measured before. 3,4,25 The water rate found for NHs adjacent to apolar blocking side chains is smaller than for alanine and increases when the peptide group basicity is increased due to neighboring polar side chains (see below). Figure 7a shows that water rates found for the dipeptide NHs (L NHs) correlate with the side chain inductive effect measured by the shift in pD min .…”
Section: Water-catalyzed Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Water catalysis has been measured before. 3,4,25 The water rate found for NHs adjacent to apolar blocking side chains is smaller than for alanine and increases when the peptide group basicity is increased due to neighboring polar side chains (see below). Figure 7a shows that water rates found for the dipeptide NHs (L NHs) correlate with the side chain inductive effect measured by the shift in pD min .…”
Section: Water-catalyzed Ratementioning
confidence: 99%
“…(3). (3) We recommend use of the activation energies specified below Table III, obtained from available results 3,4,25 and the present work weighted to account for different levels of accuracy in the various data sets. These are 14, 17, and 19 kcal/mol for k A , k B , and k w , respectively.…”
Section: Temperature Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…The reaction scheme is then change process, which in practice is a pseudo first order reaction and k3(i) is the rate constant. The exchange reaction of an amide hydrogen can take place in a reaction directly with water or it can be catalyzed by acid (hydroxonium ions) or base (hydroxide ions) (Gregory et al, 1983;Perrin, 1989), such that the observed exchange rate k,(i) is the sum of contributions from each of these three reactions.…”
Section: And O N H ( I )mentioning
confidence: 99%
“…The term k3 is the rate constant for exchange once the labile site contacts the catalyst. This second step is primarily base catalyzed above pH 4 (McDonald & Phillips, 1973;Patel & Canuel, 1976;Englander & Kallenbach, 1984), but water itself can also react directly (Gregory et al, 1983). Acid catalysis occurs at lower pH (Perrin, 1989).…”
mentioning
confidence: 99%